Utilization Of the Mendeley Application as Reference Manager For High School Teachers - Moh Mahfud Effendi; Reni Dwi Susanti (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
This study aims to describe how the Mendeley application is used in writing scientific papers by teacher representatives and to see how the effectiveness of using the Mendeley application as a References Manager. The type of research used is descriptive with a qualitative approach. Data collection was carried out by observation and questionnaires. The instruments used to retrieve data were the observation sheet and questionnaire sheet. Data analysis was carried out by reducing the data from observations and questionnaires, then the data from the reduction results were then presented in the form of tables and descriptions, which were then concluded with the results. The results showed that the Mendeley application could be used easily by teachers in compiling articles and the effectiveness of the response to using the Mendeley application as a Reference Manager also received a high percentage of 83%. And the teacher's interest in using the Mendeley application is also high, namely 81%. This is because the teacher said that Mendeley was very easy to use and up to date.